2017
DOI: 10.1111/jocn.13825
|View full text |Cite
|
Sign up to set email alerts
|

Complications of peripherally inserted central catheters in advanced cancer patients undergoing combined radiotherapy and chemotherapy

Abstract: Doctors need to be aware of the risk of peripherally inserted central catheter-related complications in patients with advanced cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
0
17
0
2
Order By: Relevance
“…However, due to patient health status, catheter implanting techniques, catheter maintenance, and other factors, complications associated with PICCs exist. 7,8 To improve the quality of PICCs, nurses have turned to advanced PICC implanting techniques. At present, PICCs are nontunneled and routinely implanted with B-mode ultrasound guidance and the modified Seldinger technique (MST).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to patient health status, catheter implanting techniques, catheter maintenance, and other factors, complications associated with PICCs exist. 7,8 To improve the quality of PICCs, nurses have turned to advanced PICC implanting techniques. At present, PICCs are nontunneled and routinely implanted with B-mode ultrasound guidance and the modified Seldinger technique (MST).…”
Section: Introductionmentioning
confidence: 99%
“…They found the overall complication rate was 53.1%: 15.1% patients exhibited PICC-related infectious complications and of which 3.9% were CLABSI; 11.4% developed PICC-related thrombosis; 9.1% were phlebitis. Comorbidity, body mass index (BMI) and duration of radio-chemotherapy were associated with PICC-related complications [19]. Bertoglio S reported 25% developed complications with 12% UEDVT and 2% CLABSI [20].…”
Section: Incidence and Risk Factors Of Picc-related Complicationsmentioning
confidence: 99%
“…Liem TK et al and Fairhall M et al have reported infection was the most common and severe complication [23]. The incidence rates of infections ranged from 3.9 to 37.9 % [19,24]. Thrombosis is considered the second major complication [23].…”
Section: Prevention Measures For Picc-related Complicationsmentioning
confidence: 99%
“…Long term CVC use is associated with an increased risk of infection. 1, 2 However, the benefits of CVC use generally outweigh the risks, and it significantly improves the quality of life of the patient receiving treatment.…”
Section: Introductionmentioning
confidence: 99%